Penerapan Regresi Peubah Ganda untuk Menentukan SNP yang Berpengaruh terhadap Prestasi Akademik SMA/MA - Wulan Andriyani Pangestu; Budi Susetyo; Rahma Anisa (Xplore: Journal of Statistics, 2018)
The evaluation step in school accreditation process includes eight components of national education standard (SNP). The result of accreditation from the evaluation is believed to explicate the academic achievement of student, in this case is National Examination (UN). Thus, it is necessary to further observe the relation between the accreditation results and the score of national examination. One of the analysis that can be used is regression analysis, it is used to observe the relation between the accreditation result and the sroce of national examination also to identify the SNP components that affect the national examination score. However, since the study was conducted at senior high school level where the national examination score for this level covers six subjects, the analysis used is no longer a simple regression but a multiple variable regression. It is because of the relationship between the score of the national examination that characterizes an academic achievement. The application result of multiple variable regression method shows that there is a relation between SNP and national examination score.